Pertumbuhan dan Kandungan Bahan Bioaktif Selaginella plana dan Selaginellla willdenovii pada Beberapa Media Tanam - Miftahudin .; Dwi Suci Setyaningsih; Tatik Chikmawati (Departemen Biologi, Institut Pertanian Bogor, 2015)
Selaginella, a genus of Pteridophyte, is known as an herb that contains of several bioactive compounds. The growth and bioactive compounds of plant were affected by plant environment, such as media types. The objective of the research was to obtain an appropriate plant media for growing S. plana dan S. willdenovii, and its effect on the content of bioactive compounds. The experiment consisted of two factors, plant growth media and the species of Selaginella. The first factor consisted of eight plant growth media, i.e.: soil, rice husk, rice husk : soil = 1:1 (v/v), burned rice husk, soil : burned rice huks = 1:1 (v/v), burned rice husk : rice husk = 1:1 (v/v), burned rice husk : rice husk = 3:1 (v/v), and burned rice husk : rice husk = 1:3 (v/v). The second factor was two spesies of Selaginella, i.e.: S. plana and S. willdenovii. Ethanol extract of Selaginella was qualitatively analyzed for flavonoid, tannin, and saponin content. The result showed that both fresh and dry weights of Selaginella were influenced by the type of plant media, Selaginella species, and their interactions. S. plana and S. willdenovii grew best on medium containing soil: burned rice = 1:1 (v/v). The highest flavonoid content of S. plana and S. willdenovii was also obtained from the plant grown on the same media. Comparing to the bioactive compound content of natural plant, saponin content of S. plana and S. willdenovii was increased by the treatment of plant media. The treatment also increased tannin content of S. plana, but not of S. willdenovii.